The use of social media marketing strategies by SMMEs in the hospitality sector in Cape Metropole, South Africa. - Obiefula Nnadi Elvis Oji; Professor Chux Gervase Iwu; Dr Norbert Haydam (African Journal of Hospitality, Tourism and Leisure, 2017)
SMMEs have been touted as the major driver of any economy – they create jobs, reduce poverty levels and generally improve the livelihood of a society. SMMEs nonetheless encounter numerous challenges. These range from lack of access to funding, poor education and understanding of small business management practices. Embedded in small business management practice, is the need to undertake proper marketing. Marketing has recently featured as one of the main challenges of small businesses. Lately, several marketing channels have emerged in response to this challenge. These channels have been reported to have positive impact. This study objective sought to determine whether social media marketing strategies are deployed within the hospitality sector in the Cape Metropole to enhance the growth of restaurants. A survey was conducted of SMMEs with employment capacity of not more than 50 employees, specifically restaurants in the Cape Metropole. A quantitative methodology was employed, using a self-administered questionnaire, distributed to SMMEs in the Cape Metropole. The sampling method was purposive. The findings of this study reveal that most of the sampled SMMEs used social media platforms. The findings also revealed that SMMEs perceive social media to have moderately effective marketing tools, with WhatsApp as the most effective, followed by Facebook and Twitter. Hence, this study provides an alternative to the ailing marketing strategies currently used by small businesses. The findings could assist SMME operators to assess and review their social media platform usage, to maximise the capabilities these platforms could offer.